2000
DOI: 10.1002/1521-3757(20001016)112:20<3702::aid-ange3702>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Katalytische asymmetrische Hetero-Diels-Alder-Reaktionen von Carbonylverbindungen und Iminen

Abstract: besonders der durch chirale Lewis-Säure-Komplexe katalysierten Variante noch gesteigert. [3] Dieser Aufsatz konzentriert sich auf die katalytischen asymmetrischen Hetero-Diels-Alder(HDA)-Reaktionen von Carbonylverbindungen und Iminen mit konjugierten Dienen [Gl. (1)]. AUFS¾TZEHetero-Diels-Alder-Reaktionen aktive HDA-Addukte entstehen. Abschlieûend werden katalytische enantioselektive Reaktionen von Iminen beschrieben. Die HDA-Reaktionen optisch aktiver Imine und Diene wurden in diesen Aufsatz aufgenommen, weil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(8 citation statements)
references
References 217 publications
0
8
0
Order By: Relevance
“…of Bu 2 Mg to 4a in [D 6 ]benzene, the well‐resolved aromatic proton signals of the free ligand 4a (Figure 1, a) were replaced by a broad bulge at 6.8–8.0 ppm (Figure 1b) which suggests the formation of some aggregated oligomeric or polymeric species in the solution. Catalyst aggregation is often a cumbersome problem for highly oxophilic metals which can lead to deactivation of the catalyst 5. Aggregation behavior for magnesium complexes has also been documented in the literature 18.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…of Bu 2 Mg to 4a in [D 6 ]benzene, the well‐resolved aromatic proton signals of the free ligand 4a (Figure 1, a) were replaced by a broad bulge at 6.8–8.0 ppm (Figure 1b) which suggests the formation of some aggregated oligomeric or polymeric species in the solution. Catalyst aggregation is often a cumbersome problem for highly oxophilic metals which can lead to deactivation of the catalyst 5. Aggregation behavior for magnesium complexes has also been documented in the literature 18.…”
Section: Resultsmentioning
confidence: 98%
“…The catalytic asymmetric hetero‐Diels–Alder (HDA) reaction of Danishefsky's diene with various aldehydes represents one of the most efficient approaches to optically active 2‐substituted 2,3‐dihydro‐4 H ‐pyran‐4‐ones, a type of six‐membered oxo heterocycle with extensive applications in natural or unnatural product synthesis 1,2. A wide variety of nonracemic catalytic systems, including both chiral Brønsted acids3,4 and chiral Lewis acids,5,6 have been developed for this type of reaction, with the latter being the focus of most current research owing to their high reactivity and facile tunability. A handful of chiral Lewis acid complexes of oxophilic metals, such as aluminium, zinc, titanium, and lanthanides, have been successfully developed for this transformation 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[216] This approach stems from a catalytic asymmetric Diels–Alder reaction [217] between dienophile 231 and diene 232 promoted by an Fe III complex with PyBOX ligand 233 (Scheme 37). Claisen rearrangement [92] of allyl enol ether 235 installed the C1 quaternary center of 236 .…”
Section: Neurotrophic Natural Productsmentioning
confidence: 99%
“…Since the discovery by Danishefsky et al5a that Lewis acids catalyze the hetero‐Diels–Alder reaction between aldehydes and electron‐rich dienes such as 1‐methoxy‐3‐(trimethylsilyloxy)butadiene (Danishefsky’s diene; see Scheme , equation b), a variety of chiral Lewis acid catalysts have been developed 5b,617. It has been shown that different metal centers like Co II ,18,19 Cu II ,20,21 Rh II ,9,22B III ,23 Al III ,6,24,25 Cr III ,7,10,11,26 Eu III ,27 Yb III ,28,29 Mn IV ,10,26 and Ti IV[15,30,31] in combination with chiral ligands containing carboxamidate,9 BINOL,3133 3,3′‐disubstituted BINOL,6,12,24 salen, [7,10,19,26,34] bisoxazoline,21,31,33,35 and triflylamide29 catalyze the HDA cycloaddition.…”
Section: Introductionmentioning
confidence: 99%